Variability in yield traits of TILLING population of bread wheat (Triticum aestivum L.) (Journal of Applied and Natural Science, 2015)
Mutagenesis is one of the powerful genetic strategies for crop improvement programmes. A chemically induced mutated genetic resource for detecting novel variations by Targeting Induced Local Lesions IN Genomes (TILLING) has been developed in recently released bread wheat (Triticum aestivum) cultivar DPW621-50. A total of 3,478 M2 plants were evaluated for plant height, number of tillers/plant, thousand grain weight, number of seeds/spike and grain yield/plant. A large variation was observed for all the traits. The highest frequency (52.2%) of lines had similar height between 91-100 cm to the non-mutagenized DPW 621-50 control followed by 28.9% of lines with height between 81-90 cm. A large variation was observed in number of tillers/plant which ranged from 1-35 tillers/plant. The highest frequency (32.09%) lines had 31-40 seeds/spike followed by 29.84% lines with 41-50 seeds/spike. Few lines (0.35%) had more than 70 seeds/spike with normal seed size as their thousand grain weight ranged between 34.82-43.82g. Chlorophyll deficient, grassy type and sterile mutants were also observed. This population may serve as new genetic resource for functional genomics studies and novel variants for different traits in elite germplasm can be made available to the plant breeders for wheat improvement.